2006
DOI: 10.1093/humrep/dei475
|View full text |Cite
|
Sign up to set email alerts
|

Serum inhibin A, VEGF and TNFα levels after triggering oocyte maturation with GnRH agonist compared with HCG in women with polycystic ovaries undergoing IVF treatment: a prospective randomized trial

Abstract: In patients with PCO treated with FSH/GnRH antagonist, final oocyte maturation with GnRH agonist instead of HCG reduces significantly inhibin A, E2 and progesterone levels during the luteal phase. This phenomenon reflects the inhibition of the corpus luteum function and may explain, at least in part, the mechanism of OHSS prevention in high-risk patients. Our results do not support a crucial role for VEGF or TNFalpha in OHSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
104
3
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(121 citation statements)
references
References 41 publications
8
104
3
6
Order By: Relevance
“…Although diff erent GnRH agonists have been used in GnRH antagonist cycles for the fi nal oocyte maturation in high-responders, no universal consensus has been defi ned regarding the optimal agonist kind and dose, and there is no report evaluating the impact of diff erent agonists on cycle outcomes. Among various GnRH agonists, buserelin 0.5 mg 14 , triptorelin 0.2 mg 15,16 and leuprolide acetate (0.5-4 mg) 17,18 have been utilized and almost all studies compared the outcomes of GnRH agonist triggered cycles with the cycles triggered with hCG. Most previous studies have reported successful oocyte maturation with 0.2-0.3 mg triptorelin, 0.5 mg buserelin and 1 mg leuprolide acetate [14][15][16]19 .…”
Section: Gnrh Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although diff erent GnRH agonists have been used in GnRH antagonist cycles for the fi nal oocyte maturation in high-responders, no universal consensus has been defi ned regarding the optimal agonist kind and dose, and there is no report evaluating the impact of diff erent agonists on cycle outcomes. Among various GnRH agonists, buserelin 0.5 mg 14 , triptorelin 0.2 mg 15,16 and leuprolide acetate (0.5-4 mg) 17,18 have been utilized and almost all studies compared the outcomes of GnRH agonist triggered cycles with the cycles triggered with hCG. Most previous studies have reported successful oocyte maturation with 0.2-0.3 mg triptorelin, 0.5 mg buserelin and 1 mg leuprolide acetate [14][15][16]19 .…”
Section: Gnrh Agonistsmentioning
confidence: 99%
“…Among various GnRH agonists, buserelin 0.5 mg 14 , triptorelin 0.2 mg 15,16 and leuprolide acetate (0.5-4 mg) 17,18 have been utilized and almost all studies compared the outcomes of GnRH agonist triggered cycles with the cycles triggered with hCG. Most previous studies have reported successful oocyte maturation with 0.2-0.3 mg triptorelin, 0.5 mg buserelin and 1 mg leuprolide acetate [14][15][16]19 . Since there is no established triggering dose, GnRH agonists may be eff ective even at lower doses because 0.1 mg triptorelin eff ectively induces fi nal oocyte maturation in IVF cycles similarly as standard doses.…”
Section: Gnrh Agonistsmentioning
confidence: 99%
“…İlk kez 2006 yılında yaptıkları ça-lışmada Babayof ve ark., OHSS için yüksek risk altında olan ve GnRHa ile tetikleme yapılan hastalarda yüksek doz östradiol ve progesteron kullanımını tanımlamışlardır, ancak bu çalışmada da reprodüktif sonuçların iyi olmadığı bildirilmiştir. 26 Sonrasında Engmann ve ark. OHSS için yüksek risk altında olan 40 yaş altı 66 hastayı dâhil ederek prospektif randomize kontrollü bir çalışma yapmışlar-dır.…”
Section: Gnrha Teti̇kleme Sonrasi Yüksek Doz öStradi̇ol Ve Progesteron unclassified
“…В не-которых исследованиях обоснована эффективность интенсивной поддержки, включающей интраваги-нальное введение микронизированного прогестеро-на или его внутримышечные инъекции в сочетании с эстрогенами, в том числе с определением уровня прогестерона (не ниже 20 нг/мл) и эстрадиола в кро-ви (не ниже 200 пмоль/л) [41,42]. Использование эстрогенов обосновано тем, что уровень эстрадиола в крови больных в протоколах с использованием аго-нистов ГнРГ ниже, чем при применении ХГ в сред-нем на 50% [43].…”
Section: почему эндометрий в протоколах стимуляции яич-ников часто явunclassified